Developmental and Psychometric Properties of a Belief-based Reproductive Health Behavior Questionnaire for Female Adolescents - Fatemeh DARABI; Mehdi YASERI; Hossein SAFARI; Mohammad Hossein KAVEH; Farideh KHALAJ ABADI FARAHANI; Davoud SHOJAEIZADEH (Tehran University of Medical Sciences, 2018)
Background: The aim of this study was to develop and evaluate the psychometric properties of a questionnaire for the measurement of reproductive health among female adolescents in Iran. Methods: This cross-sectional study was conducted among 289 female students aged 12-15 yr in Tehran, Iran from 2015-2016. The participants were selected using multi-stage random cluster sampling. In addition, the Belief-Based Reproductive Health Questionnaire (BBRHQ) was designed using the properties of the Theory of Planned Behavior (TPB). Results: Exploratory factor analysis of 104 items identified a six-factor solution. These factors jointly accounted for 67% of the observed variance of outcome variable. The confirmatory factor analysis indicated a good fit to the data. In addition, the Cronbach's alpha coefficient showed an excellent internal consistency (alpha=0.92). Conclusion: Belief-Based Reproductive Health Questionnaire (BBRHQ) is a valid and reliable instrument for measurement of reproductive health behaviors of adolescents.